Exploiting Aggregation To Achieve Phase Separation in Macrocyclization. Issue 6 (28th December 2012) - Bédard, Anne‐Catherine; Collins, Shawn K.
Abstract The aggregation properties of poly(ethylene glycol) (PEG) can be exploited in organic synthesis to control dilution effects. Through the use of solvent mixtures containing PEG400/MeOH, macrocyclization by Glaser–Hay coupling can be conducted at high concentrations. The origin of the selectivity has been studied by using surface tension measurements, UV spectroscopy, and chemical tagging and demonstrates the dependence of the yield and selectivity on the aggregation of PEG400 and its ability to preferentially solubilize organic substrates, resulting in a phase separation from the catalyst system.